Rethinking the developmental state : India's industry in comparative perspective - Pinglé, Vibha (Oxford University Press, 1999)
"Rethinking the Developmental State charts a promising new direction in political economy by detailing case studies of the relations between the state and industry. This book examines why the same state has intervened in three industries to wildly disparate levels of success. In India, the software industry has been a runaway success, the automobile industry has been moderately successful, and the steel industry has simply failed.